Quarantine and Lazarettos in the 19th Century Greece: An Economic Perspective - Dionysios D. Ithakisios; Athanassios Vozikis (SPOUDAI - Journal of Economics and Business, 2014)
This article presents the situation of public health in the 19th century Greece, with an emphasis on the financing of lazarettos. Due to "ignorance" and lack of therapeutic means and hospitals, isolation was the predominant practice for dealing with illness, both on the level of local society and also on the level of state intervention. The vast majority of the research data came from the study and the analysis-decomposition of the Annual National Reports and Annual National Budgets for the years 1822-1911. From the research findings it was unveiled that for the years up to 1863 spending on "Lazarettos and Quarantine Services" represented more than three-quarters of total health expenditures, whereas from 1864 on, due to the unfavourable financial situation, implementation of public health policy was seen to be lagging far behind. As the state became more effectively involved in the issues of health and social protection after the first decade of the 20th century, public health was not one of the top priorities of Greek governments throughout the 19th century.
Keywords: N33; I18; 330; R2; 19th century; Greece; Public Health; Quarantine; Lazarettos; Diseases and epidemics; Public Health expenditure and financing of Lazarettos